Carbon‐Doped BN Nanosheets for the Oxidative Dehydrogenation of Ethylbenzene. Issue 28 (12th June 2017) - Guo, Fangsong; Yang, Pengju; Pan, Zhiming; Cao, Xu‐Ning; Xie, Zailai; Wang, Xinchen
Abstract: Carbon‐based catalysts have demonstrated great potential for the aerobic oxidative dehydrogenation reaction (ODH). However, its widespread application is retarded by the unavoidable deactivation owing to the appearance of coking or combustion under ODH conditions. The synthesis and characterization of porous structure of BCN nanosheets as well as their application as a novel catalyst for ODH is reported. Such BCN nanosheets consist of hybridized, randomly distributed domains of h‐BN and C phases, where C, B, and N were confirmed to covalent bond in the graphene‐like layers. Our studies reveal that BCN exhibits both high activity and selectivity in oxidative dehydrogenation of ethylbenzene to styrene, as well as excellent oxidation resistance. The discovery of such a simple chemical process to synthesize highly active BCN allows the possibility of carbocatalysis to be explored. Abstract : The porous structure of two‐dimension BCN nanosheets, consisting of hybridized h‐BN and C domains, were constructed for aerobic oxidative dehydrogenation reactions. The high porosity, novel pore structure, and abundant oxygen‐containing functional groups endow the BCN with more active sites.